Optimalisasi Pelatihan Penyutradaraan untuk Meningkatkan Keterampilan dan Memperluas Peluang Masuk Dunia Kerja pada Anggota Teach4Hope di KitaBisa.com - Owie, Anggra Agastyassa; Wati, Wahyu Utami (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
This community service activity aims to improve skills and provide opportunities for orphans, poor people, and people with disabilities in the world of film through director training. The method involves the active participation of participants in the preparation, implementation, and evaluation stages. The training was held on July 7-8, 2023, at the Yogyakarta Film Academy with a focus on understanding directors, including screenplay scripts, locations, characterization, timing, and director responsibilities. A total of 15 participants produced a film entitled